PEMBINAAN KETERAMPILAN MENGAJAR SEBAGAI UPAYA PENINGKATAN KOMPETENSI GURU - Famila, Rosa; Maunah, Binti (JURNAL KOULUTUS, 2022)
Abstract : In going through the millennial era as it is today, the world of education is a very complex thing. Over time, education in Indonesia continues to show very rapid development progress. Developments in the world of education cannot be separated from the role and performance of the teacher. The role and performance of teachers greatly affect the quality of education. In achieving the goal of good quality education, it is necessary to provide guidance to teachers. Teacher performance coaching here is held to assist and serve teachers in improving the quality of knowledge, skills, attitudes, discipline, as well as meeting the needs and welfare of teachers, so that teachers have the spirit and ability to be creative and make more efforts to always improve their performance in order to improve the teaching and learning process and in achieve educational success within the institution.. Keywords: Coaching, Teacher performance, Teacher Skills